Framing the social dimension of reflection in teacher education through grounded theory and systematic review methodology - Georgia Natsiou; Melpomeni Tsitouridou (Frontiers in Education)
IntroductionAlthough peer reflection activities are a frequent choice in teacher education, inconsistencies emerge in existing literature regarding the impact of peer interaction on reflection, the design of peer reflection activities, and the visibility of the social nature of reflection. Considering those inconsistencies, the present review seeks convergence in conceptualizing the social dimension of reflection. It aims to examine how reflection is presented in relation to social interaction in the introduction of research papers that study peer reflection activities in initial teacher education.MethodsFirstly, we employed a systematic review methodology through which 98 relevant research papers were selected. Then we applied the grounded theory literature review method to seek common themes emerging in the documents of the sample.ResultsResults indicate sociality as an inherent characteristic of the reflection process substantiated in reflection definitions and social learning theoretical frameworks, and at the same time, as an acquired characteristic - a methodological choice to enhance cognitive and emotional processes of reflection. Findings also indicate that the social dimension of reflection is a fluid characteristic, constantly evolving in alignment with the social turn in learning and technology.DiscussionThe point of convergence among researchers is not the acceptance of a dominant direction in conceptualizing of the social dimension of reflection, but rather an implicit acceptance of the "fluidity" of reflection diverse approaches. Operating along a continuum between being "social by choice" and "social by nature", and evolving in response to sociocultural changes, reflection appears to overcome the absence of a consolidated theory framing its social dimension, and to be creatively founded on researchers' need to integrate it with contemporary tools and learning approaches.